Bionic research on spikes based on the tractive characteristics of ostrich foot toenail. (September 2020) - Zhang, Rui; Han, Dianlei; Yu, Guolong; Wang, Haitao; Liu, Haibao; Yu, Haibin; Li, Jianqiao
Inspired by the superior fixed and traction characteristics of ostrich foot toenails, we devised, optimized and manufactured the single structure and group arrangement of a new-style bionic spike for sprint shoes to improve athletic performance. The tractive performance of the bionic spike was tested by finite element analysis and experimental verification. The optimized single structure of the bionic spike had a top slope angle of 13° and the radius of the medial groove of 7.3 mm. Compared with the conventional conic spike, the maximal and stable extrusion resistances of the single bionic spike decreased by about 25% and 40% respectively, while the maximal and stable horizontal thrusts increased by about 16% and 10%, respectively. In addition, the arrangement of the bionic spikes was also optimized. Compared with the conventional spike group, the maximal and stable extrusion resistances of the bionic spike group decreased by 11.0% and 6.2%, respectively, while the maximal and stable horizontal thrusts increased by 20.0% and 16.0%, respectively. The current results may provide useful mechanical information that can help develop a better design of athletic shoes with the potential for advanced performance.